2022
DOI: 10.3389/fphys.2022.924750
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Chemosensory Proteins From Non-Model Insects: Advances and Perspectives in the Context of Pest Management

Abstract: Nowadays, insect chemosensation represents a key aspect of integrated pest management in the Anthropocene epoch. Olfaction-related proteins have been the focus of studies due to their function in vital processes, such ashost finding and reproduction behavior. Hence, most research has been based on the study of model insects, namely Drosophila melanogaster, Bombyx mori or Tribolium castaneum. Over the passage of time and the advance of new molecular techniques, insects considered non-models have been studied, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 259 publications
0
5
0
Order By: Relevance
“…However, the indiscriminate use of chemical pesticides seriously harms the environment and living beings [1]. The volatile chemicals already present in the environment have been extensively studied to investigate their potential role in manipulating insect behaviors, and techniques based on these behaviors are applied to integrated pest management [2]. The chemical perception of volatile chemicals in insects depends on the olfactory system, which enables insects to achieve important tasks, such as searching for food, mating, host finding, finding a place to oviposit, and even predator avoidance [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the indiscriminate use of chemical pesticides seriously harms the environment and living beings [1]. The volatile chemicals already present in the environment have been extensively studied to investigate their potential role in manipulating insect behaviors, and techniques based on these behaviors are applied to integrated pest management [2]. The chemical perception of volatile chemicals in insects depends on the olfactory system, which enables insects to achieve important tasks, such as searching for food, mating, host finding, finding a place to oviposit, and even predator avoidance [3].…”
Section: Introductionmentioning
confidence: 99%
“…Chemoreceptors are present in body hairs, appendages, mouthparts, and wings of insects (Sánchez-Gracia et al 2009). Odorant-binding proteins (OBPs) and chemosensory proteins (CSPs), which are involved in the binding and transport of odor molecules, are also expressed in tissues outside the antennae (Yi et al 2015;Lizana et al 2022). Tissue-speci c transcriptome analysis revealed that CSPs are widely expressed in both the head (including the antennae) and body tissues of adult orange spiny white ies (Gao et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…[11,16,50]. Olfactory genes play an important role in modulation of multiple behaviors, such as locating hosts and foraging mates, searching for egg-laying sites, and avoiding enemies [51,52]. Therefore, developing new strategies, based on insect olfactory perception of chemical substances such as plant volatiles is a major research direction for the future [53].…”
Section: Antennal Transcriptome Analysismentioning
confidence: 99%